Variation of Total Electron Content (TEC) during day time and night time at Malaysia's ionosphere / Mohamad Huzaimy Jusoh, Ahmad Asaris Ulaiman and Noriza Othman - Jusoh, Mohamad Huzaimy; Sulaiman, Ahmad Asari; Othman, Noriza (2008)
The ionosphere over Malaysia is unique because of its location near the equator line. Equatorial over a world are directly receive more sun radiation or ultra violet. The main purpose of this project is to study Total Electron Content (TEC) based on different time to evaluate the variation of TEC during day time and night time. The research of TEC is based on data collected from GPS receiver station at Universiti Sains Malaysia (Penang), Politeknik Ungku Omar (Ipoh) and Universiti Teknologi Mara (Arau). Normally, for every difference time the ionosphere will give difference value of TEC. From recent studies, parameter of ionosphere will change due to solar activity. The sun releases electromagnetic radiation, which is absorbed by the atmosphere around the earth. This radiation has the potential to disturb or ionize the ionosphere, the outer most layer of the atmosphere, and this then affects radio waves, including Very Low Frequency (VLF) waves, that are reflected by the ionosphere.